PELAKSANAAN FUNGSI MANAJEMEN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI (Studi Pada Kantor Camat Kambu Kota Kendari) - Audra Junita, Devanya; Tawai, Adrian; Yusuf, Muhammad (REZ PUBLICA, 2020)
This study aims 1) to find out the implementation of management functions in increasing employee work productivity at the Head Office of the Kambu District of Kendari and 2) to find out the Employee Work Productivity at the Office of the Head of Kambu District of Kendari. The design of this research is descriptive qualitative research. The population in this study were all employees working in the Kambu Camat District Office in Kendari with a total of 15 Civil Servants, not including the Kambu Camat and the Kendari Kambu Camat Secretary, who at the same time were all respondents, due to the relatively small number. To answer the problem in this research, qualitative descriptive analysis is used and supported by qualitative data. The results of this study illustrate that; 1) The implementation of management functions in the Kendari City Kambu District Office has been carried out well, this is evidenced by the answers from respondents of the four dimensions used to measure the implementation of management functions in this study. namely, the dimensions of planning, organizing, mobilizing and monitoring. 2) that the work productivity of employees at the Kambu Camat office, Kendari City, through the quality of the work of employees who are already very fast. In terms of quantity, here is also good because all organizational programs can run well and get full participation from employees. From the aspect of timeliness, it is also very good because almost all work can be completed on time, with the accuracy of the target and time in providing services have a positive impact to increase employee productivity.